PET-based polymer matrix for wires
By using a polymer matrix that recycles PET and polyolefin mixture, combined with flame retardant and antioxidant, the durability and environmental pollution of automotive cables under high temperature and oxidative stresses are solved, achieving high temperature aging and weight saving effects.
Patent Information
- Application Number
- CN202080076675.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-30
- Filing Date
- 2020-10-29
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-10-29
AI Technical Summary
Existing automotive cable insulation materials show imperfect durability under high temperature and oxidative stress, and the PVC materials used in their production process have environmental pollution problems and are difficult to meet the high temperature and long-term aging requirements of ISO 6722 standards. At the same time, the welding efficiency is subject to fat additives. The impact of
A polymer matrix consisting primarily of the recovery of polyethylene terephthalate (PET) and polyolefin mixtures was developed, with flame retardant, antioxidant and crosslinking accelerators used to manufacture automotive cable insulators, avoiding the Use plasticizers to improve welding quality and reduce environmental impact by recycling PET.
The polymer matrix achieves hydrolysis resistance and flexibility similar to PBT-based insulators, meets the high temperature aging and wear resistance of ISO 6722 standards, and significantly reduces cable weight, achieving 30% weight savings and 75% weight savings Resource savings.
Smart Images

Figure GDA0005118362890000111 
Figure GDA0005118362890000121
Abstract
Description
Technical Field
[0001] The present invention relates to polymeric materials suitable for use as insulation in electrical cables, in particular for the automotive industry. Background Art
[0002] Cars contain more and more cables, which are subject to very significant stresses, especially from temperature and oxidation. In addition, in order to limit the fuel consumption and environmental impact of cars, manufacturers seek to reduce the weight of the various materials that make up the vehicle. For this purpose, they particularly reduce the cross-section of the electrical conductors, copper strands. Typically, these strands have a cross-section of 0.35 mm 2 range, or even 0.13mm 2 Cross section of the range.
[0003] These strands are covered with an insulation material, usually based on PVC, and must be fire-resistant and abrasion-resistant while remaining flexible. In particular, they must meet the criteria set by the ISO 6722 standard, especially in terms of:
[0004] - pressure at high temperatures;
[0005] - wear and tear;
[0006] - Low temperature winding;
[0007] - Long term heat aging means more than 3000 hours.
[0008] These insulating materials, which usually consist of PVC mixtures or thermoplastic or cross-linked polyolefins, have satisfactory resistance to various stresses. In the case of PVC compounds, these insulating materials require the presence of plasticizers.
[0009] However, the use of this type of insulation creates problems during the connection of the cables, which is usually carried out by ultrasonic welding. The efficiency of this welding can be affected by the presence of some fatty additives in the composition of the insulating material, which migrate to the surface of the copper.
[0010] During extrusion and / or welding, PVC is heated to temperatures in the range of 190° C. and the plasticizers it contains (particularly liquid plasticizers of the phthalate or trimellitate type) are released and interfere with the friction properties between the conductors, which reduces the quality of the weld.
[0011] Therefore, there is still a need for companies to obtain polymer materials suitable for use as cable insulation that meet ISO 6722 standard types 2 and 3 (operating temperatures of 105° C. and 125° C., respectively, for 3000 hours) without affecting connectivization.
[0012] Alternatives have been developed to replace PVC for use in automotive cables.
[0013] For example, document WO 99 / 030330 A1 describes an electric wire made of a conductive metal wire around which an alloy of a polymer, in particular polybutylene terephthalate (PBT), is extruded. PBT is generally used to form a polymer matrix for insulation for electric cables. The properties associated with the crystal structure of PBT are known, in particular for inducing a barrier effect against molecules of small size, allowing insulation consisting of a polymer matrix comprising PBT to provide good resistance to hydrolysis.
[0014] However, these solutions require the use of virgin plastic and do not allow for the use of recycled plastic materials.
[0015] In 2016, the global production of plastics was about 396 million tons and continues to increase, especially for packaging functions, with the risk of dispersing waste in nature. The collection and recycling of these materials constitute a solution for reducing the release of waste into nature. According to Roland Geyer's opinion on plastic waste at the University of Georgia, the average recycling rate in Europe (one of the highest in the world) is only 26%.
[0016] Therefore, there is a need to develop an insulator that can have good physical properties compatible with environmental issues. Summary of the invention
[0017] After extensive research, the applicant has developed a polymer matrix comprising mainly polyethylene terephthalate PET. This matrix can be used to manufacture cables, in particular for automotive use.
[0018] The present invention therefore relates to a polymer matrix comprising:
[0019] - 50-80%, preferably 64-73% PET;
[0020] - 18-50%, preferably 20-28%, of a polyolefin mixture;
[0021] - 0.1-15%, preferably 0.2-7%, of at least one flame retardant additive;
[0022] - 0-2%, preferably 0.2-1%, of at least one antioxidant;
[0023] - 0-2%, preferably 0.2-1%, of at least one crosslinking accelerator;
[0024] - 0-2%, preferably 0.2-1%, of at least one antihydrolysis agent,
[0025] The PET is primarily recycled PET, and
[0026] The percentages are based on the total weight of the matrix.
[0027] In the present invention, "predominantly recycled PET" is understood to mean that more than 50 wt. %, preferably more than 75 wt. %, more preferably even more than 80 wt. % of the PET used in the composition is recycled PET.
[0028] Advantageously, all of the PET used in the matrix is recycled PET.
[0029] The use of recycled PET allows limiting the environmental impact associated with plastic scrap.
[0030] Advantageously, recycled PET can be obtained from unrefined recycled material.
[0031] Recycled PET for polymer matrix comes in particular from food packaging. In fact, PET, which is mainly used to make soda or mineral water bottles in particular, benefits from a mature collection and recycling chain and allows the production of food-grade rPET (recycled PET) for the production of new bottles. Colored recycled PET that cannot be used to make transparent bottles is also used to make non-food products, such as textiles or industrial fibers. Therefore, according to an embodiment of the present invention, the recycled PET comes from transparent plastic bottles, more specifically from colored plastic bottles. The bottles are first ground and washed to form flakes of variable shape, and then PET is separated from the other components of the container. The flakes are extruded to form amorphous pellets. This step allows the extraction of contaminants, such as cardboard or label residues. At the end of this step, unrefined recycled PET is obtained, which is also called amorphous recycled PET. The amorphous pellets can then be heated to 200°C for 8 hours under vacuum. This operation allows the extraction of low molecular weight components and restores the recycled PET (commonly referred to as rPET) to food grade. It also allows the extraction of residual water formed by the transesterification reaction between the heated components, which also leads to an increase in the viscosity of the polymer.
[0032] According to the invention, amorphous or crystalline PET pellets or even flakes from the first sorting can be used. Environmentally and economically, it is advantageous to use amorphous PET pellets or even flakes sorted by color or advantageously flakes of different colors, in particular from white, green or red bottles.
[0033] Furthermore, the fact that the base material may be subjected to prolonged heating without being refined allows a reduction in the processing steps for forming the polymer matrix from said material and thus further reduces the economic and environmental impact of the production process.
[0034] The amount of PET is 50-80%, preferably 64-73%. In particular, the aging properties of PET below 50% are unsatisfactory. Above 80%, the material formed by the polymer matrix is too hard and does not allow use as an insulation for cables.
[0035] In a particular embodiment, the polyolefin mixture comprises at least one polar polyolefin and possibly a non-polar polyolefin. The polar polyolefin may be selected from polar polymers containing polymerized or grafted groups, such as maleic anhydride; glycidyl methacrylate; methyl acrylate, ethyl acrylate, butyl acrylate and hexyl acrylate; acrylic acid and its salts; vinyl acetate; ethylene / methyl acrylate copolymer; ethylene / butyl acrylate copolymer; ethylene / methyl acrylate / glycidyl methacrylate terpolymer; and mixtures thereof.
[0036] When a non-polar polyolefin is present, the amount of the non-polar polyolefin is minor compared to the one or more polar polyolefins, meaning that it comprises less than 50 wt% of the total weight of the polyolefin mixture. The non-polar polyolefin is selected from the group consisting of polypropylene, polyethylene, methylpentene, polybutene, ethylene propylene diene, and mixtures thereof.
[0037] The presence of polyolefin in the polymer matrix makes the matrix sufficiently flexible and is necessary for cable applications which cannot be obtained using PET alone.
[0038] The amount of the polyolefin mixture is 18-50%, preferably 20-28%. Below 18%, the plasticizer effect is not enough to be used as an insulator for cables with small copper sections, and above 50%, the wear resistance is not enough to be used as an insulator for cables with small copper sections.
[0039] Advantageously, the flame retardant additive in the polymer matrix is selected from bromine, antimony, brominated compounds, antimony compounds or mixtures thereof, preferably antimony trioxide and decabromodiphenylalkane.
[0040] The amount of flame retardant additive is 0.1-15%, preferably 0.2-7%. This dosage is optimized to limit the technical and economic impact on the formulation as much as possible. Below 0.1%, the fire resistance will not be sufficient for automotive cable applications, while above 15%, there is no additional advantage.
[0041] The antioxidant used in the polymer matrix can be any antioxidant used in polymers. For example, it can be selected from pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), 2',3-bis[3-[3,5-di-tert-butyl-4-hydroxyphenyl]propioyl]propionohydrazide, 3,3'-thiodipropionate, or a mixture thereof. The purpose of the antioxidant is to prevent the polyolefin from oxidation.
[0042] The polymer matrix according to the invention may contain a crosslinking agent which may be 1,3,5-triallylisocyanurate or trimethylolpropanetrimethylacrylate or a mixture thereof. This crosslinking of the polyolefin phase allows to enhance the mechanical properties of the high temperature matrix in case the cable is subjected to electrons during further post-extrusion processes.
[0043] The anti-hydrolysis agent used in the matrix of the present invention is a conventional agent used in the art. Polycarbodiimide type agents can be given as examples.
[0044] According to a particular embodiment, the polymer matrix is free of plasticizers. Plasticizers are understood to mean plasticizers commonly used with PVC, in particular phthalates and trimellitates. Unlike PVC-based insulation, the polymer matrix according to the invention does not contain plasticizers and therefore does not interfere during connection.
[0045] Thus, due to the combination of PET and polyolefin, the PET-based polymer matrix according to the present invention can achieve similar flexibility characteristics to those of PVC-based matrices, and also without the addition of plasticizers.
[0046] The absence of plasticizers in the composition improves the weld quality. The resistance of ultrasonic welds is better than PVC and the quality is uniform.
[0047] The invention also relates to the use of the polymer matrix according to the invention for producing insulation for electrically conductive lines.
[0048] The invention also relates to a cable comprising at least one conducting wire covered by an insulating sleeve based on the aforementioned polymer matrix.
[0049] The cable according to the present invention is a cable commonly used for automobile wiring, having a cross-section of 0.08-0.75 mm 2 Conductive thread.
[0050] Surprisingly, even though PET is amorphous, the inventors have managed to obtain PET-based insulation with hydrolysis resistance equal to or better than PBT-based insulation.
[0051] Advantageously, cables based on recycled PET have a modulus of more than 1000 MPa, which allows them to have a wear resistance comparable to that of currently marketed cables. Thus, the recycled PET cables according to the invention have a wear resistance as good as cables formed from technical materials such as PBT, PA (polyamide) and TPE (thermoplastic polyester).
[0052] The cable consisting of a polymer matrix based on recycled PET has high temperature aging resistance that meets the requirements of the ISO 6722 standard and has high temperature pressure resistance.
[0053] Typically, cables consisting of a polymer matrix based on recycled PET have satisfactory performance in terms of ageing at temperatures between 125 and 150° C., measured according to the ISO 6722 standard.
[0054] Since there is no plasticizer in the polymer matrix of the cable of the invention, satisfactory flexibility results can be obtained.The cable consisting of the polymer matrix based on recycled PET has an elongation at break and winding at -40°C meeting the standards required by the ISO 62722 standard.
[0055] The above-mentioned properties of the insulating sleeve in terms of electrical resistance and flexibility are used to limit the thickness of the insulating sleeve without changing its properties.
[0056] As a result, the cable is thinner and the insulating sleeve is also thinner, with the result that the weight of the cable is significantly reduced. For the same performance, a weight saving of 30% is achieved compared to equivalent PVC insulation.
[0057] Furthermore, the use of recycled PET allows a significant reduction in the use of virgin material for the manufacture of insulating sleeves. For example, the use of 65% recycled PET makes it possible to use only 200g of pure material to insulate 1km of wire, compared to an average use of 950g of PVC. The use of recycled PET thus allows a 75% saving of the resources required to be achieved, which is a considerable economic and ecological advantage.
[0058] The invention also relates to the use of a cable as defined above for automotive wiring. Taking into account the weight improvement that can be obtained as described above, the cable is perfectly suited to solving the purpose of limiting environmental impact.
[0059] Another object of the present invention relates to a method for preparing a cable as described above, comprising:
[0060] - preparing a polymer matrix as defined above;
[0061] - Extruding the matrix around the electrical conductor;
[0062] - and possibly crosslinking the polymer matrix.
[0063] The following examples are presented by way of illustration only and are not to be considered limiting. DETAILED DESCRIPTION
[0064] has been passed around with 0.13mm 2 The different cables according to the invention were prepared by extruding copper strands of 0.407 mm in cross section and a diameter of 0.407 mm from the polymer matrix according to the invention.
[0065] The cables were subjected to the tests listed in Table 1.
[0066] The compositions of the polymer matrices constituting the test sleeves are given in Examples 1-6 below.
[0067] In the examples, the following commercial products were used:
[0068] ECOPET CB TH 80: recycled PET sold by Paprec
[0069] ECOFLAKES CB TH: PET in flake form sold by Paprec
[0070] ECOPET CB: PET in amorphous pellet form sold by Paprec
[0071] Irganox 1024: antioxidant sold by BASF
[0072] Irganox 1010: Antioxidant sold by BASF.
[0073] Example 1
[0074] The cable was prepared by extruding a polymer matrix having the following composition around copper wire strands:
[0075] - 64.46 wt.% ECOFLAKES CB TH,
[0076] - 23.02% by weight of ethylene methyl acrylate copolymer (methyl acrylate content 24% by weight),
[0077] - 4.60% by weight of ethylene / methyl acrylate / glycidyl methacrylate terpolymer (67 / 25 / 8),
[0078] - 2.30% by weight of antimony trioxide,
[0079] - 4.60% by weight of decabromodiphenylethane,
[0080] - 0.09 wt% Irganox 1024,
[0081] - 0.46 wt% Irganox 1010,
[0082] - 0.46% by weight of dioctadecyl 3,3'-thiodipropionate.
[0083] Extrusion was performed to give the thickness of the sleeve (from the polymer matrix) shown in Table 1. This thickness is expressed as the outer diameter of the cable.
[0084] The following characteristics are measured on the cable according to ISO6722-1-2011(E):
[0085] - resistance to flame propagation;
[0086] - abrasion resistance at 4N;
[0087] - rupture under elongation according to NF EN 60811-501 standard;
[0088] -Pressure resistance at high temperatures;
[0089] - Hydrolysis and electrolysis resistance;
[0090] - Low temperature winding;
[0091] - Heat aging at 125°C for 3000 hours.
[0092] The results of these tests are shown in Table 1, with specific conditions and / or target values shown in the first column.
[0093] Example 2
[0094] In the same manner as in Example 1, a cable obtained by extruding a polymer matrix having the following composition was prepared:
[0095] - 64.46 wt.% ECOPET CB TH,
[0096] - 23.02% by weight of ethylene methyl acrylate copolymer (methyl acrylate content 24% by weight);
[0097] - 4.60% by weight of ethylene / methyl acrylate / glycidyl methacrylate terpolymer (67 / 25 / 8),
[0098] - 2.30% by weight of antimony trioxide,
[0099] - 4.60% by weight of decabromodiphenylethane,
[0100] - 0.09 wt% Irganox 1024,
[0101] - 0.46 wt% Irganox 1010,
[0102] - 0.46% by weight of dioctadecyl 3,3'-thiodipropionate.
[0103] Extrusion was performed to give the sleeve thickness (from the polymer matrix) shown in Table 1. This thickness is expressed as the outer diameter of the cable.
[0104] The same properties as in Example 1 were measured on the cable.
[0105] The obtained values are summarized in Table 1.
[0106] Example 3
[0107] In the same manner as in Example 1, a cable was prepared by extruding a polymer matrix having the following composition:
[0108] - 64.46 wt.% ECOPET CB,
[0109] - 23.02% by weight of ethylene methyl acrylate (24%) copolymer,
[0110] - 4.60% by weight of ethylene / methyl acrylate / glycidyl methacrylate terpolymer (67 / 25 / 8),
[0111] - 2.30% by weight of antimony trioxide,
[0112] - 4.60% by weight of decabromodiphenylethane,
[0113] - 0.09 wt% Irganox 1024,
[0114] - 0.46 wt% Irganox 1010,
[0115] - 0.46% by weight of dioctadecyl 3,3'-thiodipropionate.
[0116] Extrusion was performed to give the sleeve thickness (from the polymer matrix) shown in Table 1. This thickness is expressed as the outer diameter of the cable.
[0117] The same properties as in Example 1 were measured on the cable.
[0118] The obtained values are summarized in Table 1.
[0119] Example 4
[0120] In the same manner as in Example 1, a cable was prepared by extruding a polymer matrix having the following composition:
[0121] - 73.66 wt.% ECOFLAKES CB TH,
[0122] - 13.81% by weight of ethylene methyl acrylate copolymer (methyl acrylate content 24% by weight),
[0123] - 4.60% by weight of ethylene / methyl acrylate / glycidyl methacrylate terpolymer (67 / 25 / 8),
[0124] - 2.30% by weight of antimony trioxide,
[0125] - 4.60% by weight of decabromodiphenylethane,
[0126] - 0.09 wt% Irganox 1024,
[0127] - 0.46 wt% Irganox 1010,
[0128] - 0.46% by weight of dioctadecyl 3,3'-thiodipropionate.
[0129] Extrusion was performed to give the sleeve thickness (from the polymer matrix) shown in Table 1. This thickness is expressed as the outer diameter of the cable.
[0130] The same properties as in Example 1 were measured on the cable.
[0131] The obtained values are summarized in Table 1.
[0132] Example 5
[0133] The cable was prepared by extruding a polymer matrix having the following composition around copper wire strands:
[0134] - 73.66 wt.% ECOPET CB TH,
[0135] - 13.81% by weight of ethylene methyl acrylate (24%) copolymer,
[0136] - 4.60% by weight of ethylene / methyl acrylate / glycidyl methacrylate terpolymer (67 / 25 / 8),
[0137] - 2.30% by weight of antimony trioxide,
[0138] - 4.60% by weight of decabromodiphenylethane,
[0139] - 0.09 wt% Irganox 1024,
[0140] - 0.46 wt% Irganox 1010,
[0141] - 0.46% by weight of dioctadecyl 3,3'-thiodipropionate.
[0142] Extrusion was performed to give the thickness of the sleeve (from the polymer matrix) shown in Table 1. This thickness is expressed as the outer diameter of the cable.
[0143] The same properties as in Example 1 were measured on the cable.
[0144] The obtained values are summarized in Table 1.
[0145] Example 6
[0146] The cable was prepared by extruding a polymer matrix having the following composition around copper wire strands:
[0147] - 73.66 wt.% ECOPET CB,
[0148] - 13.81% by weight of ethylene methyl acrylate (24%) copolymer,
[0149] - 4.60% by weight of ethylene / methyl acrylate / glycidyl methacrylate terpolymer (67 / 25 / 8),
[0150] - 2.30% by weight of antimony trioxide,
[0151] - 4.60% by weight of decabromodiphenylethane,
[0152] - 0.09 wt% Irganox 1024,
[0153] - 0.46 wt% Irganox 1010,
[0154] - 0.46% by weight of dioctadecyl 3,3'-thiodipropionate.
[0155] Extrusion was performed to give the sleeve thickness (from the polymer matrix) shown in Table 1. This thickness is expressed as the outer diameter of the cable.
[0156] The same properties as in Example 1 were measured on the cable.
[0157] The obtained values are summarized in Table 1.
[0158] [Table 1]
[0159]
[0160]
Claims
1. A polymer matrix, characterized in that It contains: - 50-80% PET; - 18-50% polyolefin blend; - 0.1-15% of at least one flame retardant additive; - 0.2-1% of at least one antioxidant; - 0-2% of at least one crosslinking accelerator; - 0-2% of at least one anti-hydrolysis agent, The percentages are based on the total weight of the matrix and are characterized in that: - more than 50% by weight of the PET is recycled PET; - the polyolefin mixture is a mixture of ethylene / methyl acrylate copolymer and ethylene / methyl acrylate / glycidyl methacrylate terpolymer; - the flame retardant additive is selected from brominated compounds, antimony compounds or mixtures thereof; The antioxidant is selected from pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), Irganox 1024, distearyl 3,3'-thiodipropionate, or a mixture thereof.
2. The polymer matrix according to claim 1, characterized in that The PET is recycled.
3. The polymer matrix according to claim 1 or 2, characterized in that The recycled PET comes from food packaging.
4. The polymer matrix according to claim 1, characterized in that The flame retardant additive is antimony trioxide and / or decabromodiphenylethane. 5 . The polymer matrix according to claim 1 , which contains a crosslinking accelerator, wherein the crosslinking accelerator is triallyl 1,3,5-isocyanurate or trimethylolpropane trimethacrylate.
6. The polymer matrix according to claim 1, characterized in that It contains no plasticizers.
7. Use of a polymer matrix as defined in any one of claims 1 to 6 for producing insulation for electrically conductive wires.
8. Cable comprising at least one conducting wire covered by a protective sleeve based on a polymer matrix as defined in any one of claims 1 to 6.
9. Use of a cable as defined in claim 8 for automotive wiring.
10. A method for preparing a cable according to claim 8, comprising: - preparing a polymer matrix as defined in any one of claims 1 to 6; - Extruding the matrix around the electrical conductor; - and optionally crosslinking the polymer matrix.
Citation Information
Patent Citations
Electric wire with thin insulation based on polybutyleneterephthalate
WO1999030330A1
Preparation method of modified polyethylene terephthalate cable sheath tube
CN102604338A
Preparation method of high-heat-resistance high-strength half tubes used for embedded electric cables
CN102604339A
Recycled pet resin composition, composition for modifying recycled pet resin and molded product of recycled pet resin
JP2005105055A
Multi-layer insulated wire, processes for preparing the same, and its applications
US20050252679A1